40 Relationship among gastrointestinal nematode infection indicators in meat goat kids. (7th December 2018) - O'Brien, D; Schoenian, S; Semler, J; Gordon, D; Bennett, M
Abstract: A pasture-based meat goat performance test was conducted at the University of Maryland's Western Maryland Research & Education Center (39º 30' N/77º 44' W) from 2007–2016. The purpose of the test was to evaluate the performance of meat goat bucklings (mostly Kiko and Kiko crosses), consuming a pasture-based diet, with natural exposure to gastro-intestinal parasites. While on test, the goats were handled bi-weekly to determine body weights (BW), FAMACHA© scores (FAM) and body condition (BCS) scores. Coat condition (COAT), dag (DAG) and diarrhea scores (DISCO) and deworming frequency (TX) were also recorded from 2012–2016. Fecal samples were collected bi-weekly to determine individual fecal eggs counts (FEC; 2007–2016) and pooled samples were collected every 28 days for larvae ID (2009–2016). Data came from 811 meat goat kids representing 100 herds in 20 states. Residual correlations among log-transformed FEC (LFEC), FAMACHA© scores, BW, ADG, BCS, coat condition, dag and fecal consistency scores were determined. In addition, deworming frequency by year was determined by PROC FREQ in SAS. The predominant genera of gastrointestinal nematode cultured was Haemonchus contortus ranging from 70–95% over the 10-yrs. Overall, residual correlations (r) of FAMACHA scores with ADG (-0.15), LFEC (0.24), BCS (-0.09), COAT (-0.06), DAG (0.12) and DISCO (0.04) were significant ( P<0.05). Correlations of LFEC with ADG (-0.07), BCS (-0.07), COAT (-0.06) and DISCO (0.06) were significant ( P< 0.01) but LFEC was not significantly correlated with DAG scores (0.03, P= 0.16). Within years, the correlation between LFEC and FAM varied (0.10–0.38) but were significant for all years with the exception of 2007 (0.10, P= 0.16). Deworming frequency also varied by year, ranging from 18.5–29.6% and highest in 2013. Results demonstrate that higher FAMACHA© scores are associated with increased FEC, more runny stools and fecal soiling in slower growing, less conditioned meat goat kids with rougher coats.